SYSTEM INTEGRATED FAULT-TREE ANALYSIS METHODS (SIFTAN) - RUTENBERG, MARK, R (1989)
The subject invention employs a system integrated fault-tree analysis (SIFTAN) which has the unique ability to detect all latent hardware and software design defects that could cause unanticipated critical failure of a complex software controlled electronic system. This new approach modifies and then integrates two existing system analysis techniques-namely, hardware fault-tree analysis (HFTA) and software fault-tree analysis (SFTA). The resultant integrated technique is identified as SIFTAN for system integrated fault-tree analysis. Through its integrated hardware/software scope and its critical failure focus, SIFTAN has unique potential to solve the essential analytical limitation behind the software reliability problem. The system exceeds the scope of all current system analysis techniques by providing a system free from all potential critical specification hardware or software design errors. The system accomplishes the above-noted objects by performing fault-tree analysis with respect to the contents of a dynamic ''stack of contradiction parameters'' and then superimposing the modified hardware and software fault-trees onto each other. The superposition is accomplished by automatically branching from the software to a specified fault-tree hardware whenever hardware could result in a critical system output. It is important to indicate that the SIFTAN system is applied with great advantages to early conceptual levels of system design in addition to its certification of the final design implementation.